Criminal liability for the breaking of inviolability of private life: analysis of new edition of Article 182 of Criminal Code of Ukraine - Дем’яненко, Ю. І. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article is dedicated to analysis of new edition of Article 182 of Criminal Code of Ukraine. Major attentionwas attached to consideration of new legislative statements on criminal liability for the illegal actionsagainst confidential information private person.